THE INFLUENCE OF PRODUCTS AND PROMOTIONS ON PURCHASING DECISIONS MEDIATED IN PURCHASE MOTIVATION - Aji, Nugroho Setio; Djawahir, Achmad Helmy; Rofiq, Ainur (Universitas Brawijaya, Indonesia, 2019)
This study aims to test and analyze the effect of product and promotion on buying decision mediated purchasing motivation. This research is quantitative research with explanatory research approach. This research is conducted on a fixed consumer who partnered with PT. TrakindoUtama Surabaya more than three years amounted to 58 respondents. Data collection using questionnaire and literature review with WarpPLS version 6.0 analysis tool. The results of the study showed that the direct effect of product influence on purchase motivation and the influence of promotion on purchasing motivation had a strong significant influence. Furthermore, the influence of the product on purchasing decisions and the influence of promotion on purchasing decisions have a significant weak influence. Next, the effect of purchasing motivation on purchasing decisions has a significant weak influence. Also, indirectly the motivation of purchase can mediate the effect of the product on purchasing decisions because it has a strong significant influence. However, the indirect effect of purchase motivation cannot mediate the influence of promotion on purchasing decisions, because it has a weak significant influence.